Chloromethyl-triazole: a new motif for site-selective pseudo-acylation of proteins. Issue 82 (26th September 2016) - Brewster, Richard C.; Gavins, Georgina C.; Günthardt, Barbara; Farr, Sarah; Webb, Kimberly M.; Voigt, Philipp; Hulme, Alison N.
Abstract : Chloromethyl triazoles are shown to be cysteine selective alkylation reagents for 'near-native' post-translational modification of protein and peptide substrates. Abstract : Rapid, site-selective modification of cysteine residues with chloromethyl-triazole derivatives generates pseudo-acyl sLys motifs, mimicking important post-translational modifications. Near-native biotinylation of peptide and protein substrates is shown to be site-selective and modified histone H4 retains functional activity.